STUDENTS' SATISFACTION WITH ONLINE COUNSELING SERVICES DURING THE COVID-19 OUTBREAK IN INDONESIA - Arga Satrio Prabowo (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
The Covid-19 pandemic that struck Indonesia and the world has significantly changed human life. The change occurs in various lines, such as in the social, economic, and even educational sectors experienced significant changes due to the impact of the Covid-19 pandemic. This significant change impacts the number of psychological disorders experienced by the community, including students. The high number of students who experience psychological disorders during this learning period from home has led higher education institutions to organize online counseling services. This study aims to reveal respondents' satisfaction after implementing online counseling. This study involved 61 students with experience participating in online counseling services organized by the Guidance and Counseling Department of Sultan Ageng Tirtayasa University Indonesia during the distance learning period during the Covid-19 pandemic. The method used in this research is the descriptive research method. This study found that 90.39% of research respondents were satisfied after online counseling. The results of this study can be a reference for counselors both within educational institutions and outside formal educational institutions to carry out counseling using online methods.